Effectiveness and safety of acupuncture combined with traditional Chinese medicine in the treatment of chronic prostatitis: A systematic review and meta-analysis. Issue 49 (10th December 2021) - Li, Chenxi; Xu, Lei; Lin, Xuyao; Li, Qingrui; Ye, Pule; Wu, Lin; Wang, Mingkai; Li, Lichao; Li, Lanlan; Zhang, Yue; Li, Hua; Qin, Guozheng
Abstract: Objective: Chronic prostatitis (CP) is a common disease in the outpatient department of males and urology. Clinical studies have found that acupuncture combined with traditional Chinese medicine (TCM) has achieved good results in treating CP, but its efficacy and safety are not completely clear. This study aimed to investigate the efficacy and safety of acupuncture combined with TCM in the treatment of CP. Methods: Randomized controlled trials of acupuncture combined with TCM in treating CP were screened by searching PubMed, Embase, Cochrane Library, CNKI, etc. The retrieval time was from the database establishment date to March 31, 2021. The Cochrane Collaborative Risk Bias Assessment tool was used to evaluate literature's methodological quality of the literature. The RevMan5.4 software was used for the meta-analysis of outcome indicators. The TSA v0.9 software was used for sequential trial analysis (TSA) of effectiveness. Results: In this study, 19 related randomized controlled trial studies were included, with a total of 1831 cases. The results of the meta-analysis showed that acupuncture combined with TCM could significantly improve the clinical efficacy of CP (OR = 3.76, 95%CI: 2.82 to 5.02, P < .00001), reduce the total score of The National Institutes of Health chronic prostatitis symptom index (MD = −4.00, 95%CI: −4.67 to 3.33, P < .00001), and improve patients' urination symptoms (MD = −1.10, 95%CI: −1.23 to −0.97, P < .00001), alleviated the pain symptoms of patients (MD = −2.38, 95%CI: −2.41 to −2.35, P < .00001), improved the quality of life of patients (MD = −1.69, 95%CI: −1.97 to −1.41, P < .00001), decreased the scores of TCM symptoms of patients (MD = −2.39, 95%CI: −3.45 to −1.33, P < .00001), and did not increase the adverse reactions of patients (MD = 1.09, 95%CI: 0.57 to 2.06, P = .8). The results of publication bias showed that this study was not affected by publication bias, and the conclusion was reliable. TSA showed that acupuncture combined with TCM was effective in treating CP. Conclusion: Acupuncture combined with TCM is safe and effective for alleviating CP. It can be used as an effective treatment for chronic prostatitis in the clinic. Registration number: DOI 10.17605/OSF.IO/Z8FJM.